U źródeł świętości. Wokół problemu początków kultu św. Teodozego - ihumena Ławry Peczerskiej w Kijowie - Bartnicki Mariusz (Saeculum Christianum, 2022)
The article depicts the circumstances of the origin of the cult of St. Theodosius, ihumen of the Kiev-Pechersk monastery. The text analyzes the preserved sources (The Tale of Bygone Years, The Kie- Pechersk Patericon) concerning the events of the translation of Theodosius’ remains to the monastery church of the Dormition of the Mother of God, which, in the opinion of many researchers, gave rise to the cult of the saint. The examination of this issue allows for a thesis that the events of 1091 could have resulted from prosaic reasons – the right of ihumen to be buried in the monastery church as well as the fact that he was one of the initiators of the construction of the temple. The textological observations also make it possible to question the chronology of events related to the formation of the cult of Theodosius, as presented in the Tale of Bygone Years, which was based on the Life of St. Theodore the Studite, as can be assumed. The beginning of the cult of St. Theodosius was associated with cultural changes, whose first symptoms can be observed in Ruthenia in the first decade of the 12th century. At that time, the Metropolitan of Kiev, Nikifor I, entered the name of Theodosius in Sinodik, officially including him among the saints of the Church of Kievan Rus.